Análisis Del Problema Del Contrabando De Gasolina De Colombia A Venezuela (2024)
Colombia shares a border of approximately 2,219 kilometers with the Republic of Venezuela, which has allowed a commercial, economic and cultural exchange that throughout history has brought benefits to both nations. However, this exchange of products and services has not only generated legitimate commercial activities, but, due to the Venezuelan currency exchange crisis and the difference in the purchasing power of the currencies of both countries, has led to illegal fuel trafficking or smuggling.